The pricing of sentiment risk in European stock markets - Karl Ludwig Keiber; Helene Samyschew (European University Viadrina, Department of Business Administration and Economics, 2016)
This paper studies whether sentiment is rewarded with a significant risk premium on the European stock markets. We examine several sentiment proxies and identify the Economic Sentiment Indicator (ESI) from the EU Commission as the most relevant sentiment proxy for our sample. The analysis is performed for the contemporaneous excess returns of eleven euro area (EA-11) stock markets in the period from February 1999 to September 2015. We apply a conditional multiplebeta pricing model in order to track the variation of the sentiment risk premium over time. The results demonstrate a positive significant relationship between sentiment and contemporaneous excess returns which is consistent to the previous studies. The calculated sentiment risk premium is significant as well but of a negative sign implying that an investment in EA-11 countries over the examined time period would have been unattractive to the investors on average.
Keywords: G12; G15; 330; international asset pricing; European risk premia; sentiment risk; conditional asset-pricing model